The Egyptian Labour Market, Determinants of Employment and Wage Estimation - Alattas, Halah; Alimam, Haga (European Journal of Sustainable Development, 2022)
This study empirically evaluates the factors influencing employment in Egypt by using the recently published cross-sectional Egyptian Labour Force Survey, 2019. The logistic regression analysis revealed that being older, male, married, and living in a rural region increased the probability of an individual being employed. Contrary to the assumption of the human capital theory, the attainment of all education levels appeared to reduce the likelihood of attaining employment in the Egyptian labour market. Moreover, the multiple linear regression reveals significant factors influencing wage estimation in the Egyptian labour market. Some of those factors were related to individual characteristics, while others related to employer characteristics, emphasising the critical role of both sides of the labour market in estimating wages. However, other socioeconomic factors should be determined in order to increase the overall model interpretation.